A survey on enhanced power graphs of finite groups - Xuanlong Ma; Andrei Kelarev; Yuqing Lin; Kaishun Wang (Electronic Journal of Graph Theory and Applications (EJGTA), 2022)
We survey known results on enhanced power graphs of finite groups. Open problems, questions and suggestions for future work are also included.